2007
DOI: 10.1007/s10695-007-9180-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of over-wintering common carp (Cyprinus carpio) to disturbance by Eurasian otter (Lutra lutra)

Abstract: Using a tame animal, the impact of otter (Lutra lutra) disturbance on over-wintering carp (Cyprinus carpio) was monitored in two experiments, 133 and 140 days, respectively, over two consecutive winters (November-April). The level of stress in over-wintering carp exposed to various intensities of disturbance by otters was quantified using biological indicators of stress (cortisol, cortisone, indices of nitrogen, carbohydrate, lipid and mineral metabolism and activity of basic blood plasma enzymes) taken from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Gluconeogenesis of proteins should increase excretion of nitrogen wastes in the forms of ammonia, uric acid, or urea. Elevated levels of urea were found in European carp that were exposed to chronic risk of otter predation (Polednik et al 2008). Increased excretion of N-rich compounds should lead to an increase in the overall body C : N ratio.…”
Section: Consequences Of Chronic Stress Responses To Predation Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…Gluconeogenesis of proteins should increase excretion of nitrogen wastes in the forms of ammonia, uric acid, or urea. Elevated levels of urea were found in European carp that were exposed to chronic risk of otter predation (Polednik et al 2008). Increased excretion of N-rich compounds should lead to an increase in the overall body C : N ratio.…”
Section: Consequences Of Chronic Stress Responses To Predation Riskmentioning
confidence: 98%
“…Chronic predation risk leads to changes in prey body composition expected after the induction of gluconeogenesis. Chronic risk of dragonfly predation decreased protein content in damselflies (Stoks et al 2005) and increased glucose content in European carp (Polednik et al 2008), snow hares (Boonstra et al 1998), and Arctic ground squirrels (Hik et al 2001). Song sparrows exposed to elevated risk of predation increase free fatty acids levels relative to those of sparrows from lower-risk habitats (Clinchy et al 2004).…”
Section: Consequences Of Chronic Stress Responses To Predation Riskmentioning
confidence: 99%
“…These enzymes leak into blood plasma as a consequence of tissue damage or dysfunction (Ciereszko et al 1998;Oluah 1999). They had been extensively used to monitor the physiological status of fishes exposed to stressful conditions (Wells et al 1986;Poledník et al 2008). Another response that can help evaluate the effect of temperature is red blood cells (RBC) count.…”
Section: Introductionmentioning
confidence: 99%
“…No other data dealing with the phenomenon of fish displacement due to cormorants feeding habits have been recorded or published so far. Fish stress response to disturbances caused by piscivorous predators was also studied by Poledník et al (2008) who observed the impact of Eurasian otter (Lutra lutra) feeding on the stock of carp ponds. The study was based on plasma biochemical indices assessments aimed at cortisol, glucose and lactate concentrations.…”
Section: Discussionmentioning
confidence: 99%